Correction: Significance of major international seaports in the distribution of murine typhus in Taiwan. - Chi-Chien Kuo; Nicola Wardrop; Chung-Te Chang; Hsi-Chieh Wang; Peter M Atkinson (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005430.].